The Effectiveness of Using a Fruit Carving Application in Enhancing Fruit Carving Skills in the Food Decoration Course at the Culinary arts Vocational Education Program - Damayanti Trisnasari; Sam Hermansyah; Usman M; Hartati , Hartati; Muh. Ananda Nahdatullah (Edumaspul: Jurnal Pendidikan, 2024)
The Android-based Fruit Carving application serves as a learning media for food decoration, providing an opportunity for students in the Culinary Arts Vocational Education Program at Universitas Muhammadiyah Sidenreng Rappang to interact with learning materials using smartphones. By applying the drill and practice method, the application allows students to practice fruit carving techniques repeatedly, which helps improve their skills through constant repetition. This learning approach not only refines their practical abilities but also fosters habits that lead to mastery. As students continue to practice, their competency in fruit carving as a food decoration skill increases, ultimately contributing to their overall professional development in the culinary arts. This study highlights the potential of integrating mobile technology into vocational education, offering a more accessible and flexible way to enhance students' skills and competence.